Co-assembly method for improving energy transfer efficiency of chromophore, co-assembly body and application
Through the crystallization-induced precise co-assembly method, donor, acceptor and perfluoroaromatic hydrocarbons are co-assembled and inserted into the crystal lattice, solving the problems of high energy dissipation and low FRET efficiency of weakly aggregated emitter donor-acceptor pairs during fluorescence resonance energy transfer, and achieving efficient FRET process and color adjustment.
Patent Information
- Application Number
- CN202411300767.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-18
- Publication Date
- 2025-03-04
- Estimated Expiration
- 2044-09-18
AI Technical Summary
The problem of high energy dissipation and low FRET efficiency of donor-acceptor pairs with weakly aggregated state emissions.
By crystallization-induced precise co-assembly method, the donor substance, the acceptor substance and the perfluoroaromatic hydrocarbon are co-assembled under a solvent system, and the perfluoroaromatic hydrocarbon is inserted into the crystal lattice of the donor and the acceptor to prepare a co-assembly.
It significantly improves the efficiency of fluorescence resonance energy transfer, improves up to 180% to 270%, and adjusts the color and brightness, from monotonous yellow, orange, and black to color, brighter green, yellow, orange, and red.
Smart Images

Figure CN119552047A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of organic photoelectric materials, and in particular to a co-assembly method, a co-assembly body and an application thereof for improving the energy transfer efficiency of chromophores. Background Art
[0002] π-Conjugated organic optoelectronic materials are indispensable materials for the development of advanced electronic information devices and biodiagnostic / therapeutic methods. The properties of these materials are closely related to one or more physical processes, such as electron excitation and emission, upconversion, electron and hole transport, energy transfer, light harvesting, etc.
[0003] Fluorescence resonance energy transfer, abbreviated as FRET, is a non-radiative energy electronic excitation transfer process based on the long-range dipole-dipole interaction between the energy donor and the acceptor. It has attracted much attention due to its unique characteristics and broad application prospects. FRET mainly involves the energy transfer of two fluorescent groups, the donor and the acceptor. When the donor fluorescent group is excited, if its emission spectrum overlaps with the absorption spectrum of the acceptor fluorescent group, the donor can transfer energy to the acceptor non-radiatively, thereby changing the fluorescence intensity and lifetime of both. The FRET efficiency is highly dependent on the distance between the donor and the acceptor, which is usually in the range of 1nm to 10nm, and decreases rapidly with the increase of the distance. In addition, the degree of spectral overlap between the donor and the acceptor and the parallelism of the transition dipole direction are also key factors affecting the FRET efficiency.
[0004] At present, FRET has been widely used in many fields such as optoelectronic devices, fluorescence detectors, life sciences, environmental monitoring, nanomaterials, luminescent quantum dots, functional supramolecular materials, etc. Among them, in life sciences, FRET with high fluorescence quantum yield is used as a spectral molecular ruler to measure the distance and conformational changes between biological molecules, such as protein-protein interactions and DNA hybridization. This is a simple and effective super-resolution optical measurement technology that can provide real-time, in situ detection without any intervention. In the field of optoelectronic devices, FRET is used to regulate and improve the performance of optoelectronic materials, such as solar cells, photodetectors and LEDs. It can be seen that the precise regulation of FRET efficiency is crucial to improving the performance of organic optoelectronic materials, but this is still a key issue that needs to be solved urgently.
[0005] There are several methods to improve the efficiency of FRET. Among them, adjusting the distance between the donor and the acceptor is one of the most commonly used methods, but this requires precise nanoscale control and is difficult to operate in practice. In addition, by controlling the number of acceptors around the donor, changing the degree of donor-acceptor spectral overlap, or changing the parallelism of the transition dipole direction of the donor-acceptor pair, the FRET efficiency can also be improved to a certain extent, but these methods also have problems such as complex operation and time-consuming.
[0006] In addition, the reported FRET is mainly limited to chromophores with high aggregate emission, while it is difficult to achieve efficient FRET in the weak emission state, resulting in the problems of high energy dissipation and low FRET efficiency in the fluorescence resonance energy transfer process of donor-acceptor pairs with weak aggregate emission. Summary of the invention
[0007] In order to solve the problems of high energy dissipation and low FRET efficiency in the fluorescence resonance energy transfer process of donor-acceptor pairs with weak aggregated emission, the purpose of the present invention is to provide a co-assembly method, co-assembly and application for improving the energy transfer efficiency of chromophores.
[0008] To achieve the above objectives, the technical solution of the present invention is as follows.
[0009] The first aspect of the present invention provides a crystallization-induced precise co-assembly method for improving FRET efficiency, comprising the following steps:
[0010] A donor substance and a perfluoroarene are co-assembled in a solvent system to prepare a donor-perfluoroarene complex; an acceptor substance and a perfluoroarene are co-assembled in a solvent system to prepare an acceptor-perfluoroarene complex; the donor-perfluoroarene complex and the acceptor-perfluoroarene complex are co-assembled in a solvent system, and the perfluoroarene is inserted into the crystal lattices of the donor substance and the acceptor substance during the co-assembly process to prepare a co-assembly; the donor substance is 9,10-bis(phenylethynyl)anthracene; the acceptor substance is 5,12-bis(phenylethynyl)tetracene; and the perfluoroarene is octafluoronaphthalene.
[0011] Preferably, the ratio of the total molar amount of the acceptor substance and the donor substance to the molar amount of the perfluoroarene is 1: 1. Preferably, the molar amount of the acceptor substance accounts for 0.3% to 22.4% of the total molar amount of the donor substance and the acceptor substance.
[0012] Preferably, the solvents used to prepare the donor-perfluoroarene complex, the acceptor-perfluoroarene complex and the co-assembly are selected from at least one of chloroform, N,N-dimethylformamide, tetrahydrofuran, acetone and acetonitrile. Preferably, the co-assembly is wet-milled in a solvent system, or volatilized in a solvent system to remove the solvent. The co-assembly operation is carried out at room temperature, and octafluoronaphthalene, 9,10-bis(phenylethynyl)anthracene and 5,12-bis(phenylethynyl)tetracene are all solid at room temperature. Volatilization is carried out at room temperature and atmospheric pressure. Specifically, during wet milling, the ratio of solid matter to solvent is 10 mg:0.05 mL; during volatilization, the ratio of solid matter to solvent is 1 mg:1 mL.
[0013] Preferably, in the co-assembly, the average distance between the donor substance and the acceptor substance is 0.69-0.7 nm.
[0014] The second aspect of the present invention provides a co-assembly, wherein the co-assembly is prepared by the co-assembly method for improving the chromophore energy transfer efficiency described in the first aspect.
[0015] Preferably, the co-assembly is obtained by co-assembling a donor-perfluoroarene complex and an acceptor-perfluoroarene complex, and the perfluoroarene is inserted into the lattice of the donor substance and the acceptor substance during the co-assembly process, so that the average distance between the donor substance and the acceptor substance is 0.69nm to 0.7nm.
[0016] Preferably, the crystal parameters of the donor-perfluoroarene complex are: The crystal parameters of the donor-perfluoroarene complex are: monoclinic space group P21 / c, unit cell parameters α=90°, β=104.471(5)°, γ=90° and Preferably, the crystal parameters of the receptor-perfluoroarene complex are: monoclinic space group P21 / c, unit cell parameters α=90°, β=100.157(5)°, γ=90°,
[0017] The third aspect of the present invention provides a use of the co-assembly described in the second aspect in preparing water-phase luminescent ink.
[0018] Beneficial effects of the present invention:
[0019] 1. The present invention mainly uses 9,10-bis(phenylethynyl)anthracene with significant aggregate fluorescence quenching effect as the donor substance of fluorescence resonance energy transfer, 5,12-bis(phenylethynyl)tetracene as the acceptor substance of fluorescence resonance energy transfer, and weakly fluorescent octafluoronaphthalene as the molecular igniter; the perfluoroaromatic hydrocarbons are inserted into the lattices of the donor substance and the acceptor substance by a co-assembly method, and the fluorescence resonance energy transfer efficiency is improved by up to 180% to 270%, thereby solving the problems of high energy dissipation and low FRET efficiency of the donor-acceptor pair with weak aggregate emission in the fluorescence resonance energy transfer process.
[0020] 2. The present invention can induce precise co-assembly through crystallization, and can adjust the color and brightness from monotonous, weakly emitting yellow, orange, and black to colorful, brighter emitting green, yellow-green, yellow, orange, and red. Based on this, the present invention successfully produces different multi-stimulus responsive fluorescence patterns and highly flexible, highly luminous colored flowers, greatly broadening the application field of the co-assembly provided by the present invention. BRIEF DESCRIPTION OF THE DRAWINGS
[0021] Figure 1 Figure a is the co-assembly principle diagram of BPA-OFN in Example 3; Figure b is 0.1 mg mL -1 Photographs of BPA solution, BPA solid, and BPA-OFN co-crystals under 365 nm ultraviolet irradiation.
[0022] Figure 2 Figure a is the co-assembly principle diagram of BPN-OFN in Example 4; Figure b is 0.1 mg mL -1 Photographs of BPN solution, BPN solid, and BPN-OFN co-crystal under 365 nm ultraviolet irradiation.
[0023] Figure 3 In the figure, Figure a is the infrared spectra of OFN, BPA and BPA-OFN of Example 3; Figure b is the infrared spectra of OFN, BPN and BPN-OFN of Example 4.
[0024] Figure 4 In the figure, Figure a is the Raman spectra of BPA and BPA-OFN of Example 3; Figure b is the Raman spectra of BPN and BPN-OFN of Example 4.
[0025] Figure 5 In the figure, Figure a shows the experimental and calculated PXRD spectra of BPA-OFN co-crystal and the experimental PXRD spectra of OFN and BPA; Figure b shows the experimental and calculated PXRD spectra of BPN-OFN co-crystal and the experimental PXRD spectra of OFN and BPN.
[0026] Figure 6In the figure, Figure a is the absorption spectrum and photoluminescence spectrum of BPA solution, BPA solid and BPA-OFN of Example 3; Figure b is the absorption spectrum and photoluminescence spectrum of BPN solution, BPN solid and BPN-OFN of Example 4.
[0027] Figure 7 In the figure, C is the molecular orbital diagram of BPA-OFN; D is the molecular orbital diagram of BPN-OFN; E is the molecular mixed stacking structure of BPA-OFN; F is the molecular mixed stacking structure of BPN-OFN; G is the growth morphology of BPA-OFN co-crystal; H is the growth morphology of BPN-OFN co-crystal. The insets of G and H are the corresponding low-magnification transmission electron microscope images.
[0028] Figure 8 In the figure, Figure a is the absorption spectrum of BPN and the photoluminescence spectrum of BPA; Figure b is the absorption spectrum of BPA@BPN at different doping ratios; Figure c is the photoluminescence spectrum of BPA@BPN at different doping ratios; Figure d is the time-resolved fluorescence decay diagram of BPA@BPN at different doping ratios; the inset of Figure d is the corresponding photograph under ultraviolet light; Figure e is the absorption spectrum of BPN-OFN and the photoluminescence spectrum of BPA-OFN; Figure f is the absorption spectrum of BPA-OFN@BPN-OFN at different doping ratios; Figure g is the photoluminescence spectrum of BPA-OFN@BPN-OFN at different doping ratios; Figure h is the time-resolved fluorescence decay diagram of BPA-OFN@BPN-OFN at different doping ratios; the inset of Figure h is the corresponding photograph under ultraviolet light.
[0029] Fig. 9 FM images of BPA-OFN@BPN-OFN microrods under 365nm excitation. From a to e, the doping ratios of BPN-OFN are 0, 0.3, 3.7, 22.4 and 100%, respectively.
[0030] Fig.10 The PXRD spectra of the five samples are shown in Figure 2.
[0031] Fig.11 are the CIE coordinate values corresponding to the five samples.
[0032] Fig.12 Schematic diagram of the energy transfer mechanism.
[0033] Fig.13Figure a shows a picture of the letters of FRET and By XJTU and a cartoon picture of a thumb drawn with a brush dipped in yellow BPA and black BPN ink respectively under visible light; Figure b shows a picture of Figure a under ultraviolet light; Figure c shows b after being stimulated by OFN solution; Figure d shows c after being further stimulated by BPN / OFN solution; Figure e shows a schematic diagram of the preparation of highly luminescent films and three highly luminescent flowers, as well as photos under sunlight and ultraviolet light. DETAILED DESCRIPTION
[0034] In order to make the purpose, technical solution and advantages of the present invention more clearly understood, the present invention is further described in detail below in conjunction with the embodiments. It should be understood that the specific embodiments described herein are only used to explain the present invention and are not used to limit the present invention.
[0035] Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in the field without making any creative work shall fall within the scope of protection of the present invention.
[0036] Aggregation-Caused Quenching, abbreviated as ACQ. 9,10-Bis(Phenylethynyl)Anthracene, abbreviated as BPA, has a structural formula of 5,12-Bis(2-Phenylethynyl)-naphthacene, the full name of which is 5,12-Bis(2-Phenylethynyl)-Naphthacene, abbreviated as BPN, has the structural formula Octafluoronaphthalene, the full name of which is Octafluoronaphthalene, abbreviated as OFN, has the structural formula BPA is used as the donor substance of fluorescence resonance energy transfer; BPN is used as the acceptor substance of fluorescence resonance energy transfer. Weakly fluorescent octafluoronaphthalene is used as a molecular igniter. Photoluminescence quantum yield, the full name in English is Photoluminescence Quantum Yield, abbreviated as PLQY.
[0037] Reported FRET is mainly limited to chromophores with high aggregate emission, while it is difficult to achieve effective FRET in weak emission states. This is because most of the energy will be dissipated through non-radiative processes during the transfer process, including intersystem crossing, singlet fission, etc., resulting in a significant reduction in energy utilization efficiency. Therefore, it is a huge challenge to achieve effective FRET between donor-acceptor pairs with weak aggregate emission.
[0038] The present invention develops a strategy, namely a crystallization-induced precise co-assembly method, to effectively improve the fluorescence resonance energy transfer efficiency of ACQ chromophores. The present invention selects 9,10-bis(phenylethynyl)anthracene and bis(phenylethynyl)tetracene with significant ACQ effect as donor and acceptor substances for fluorescence resonance energy transfer, respectively, and weakly fluorescent octafluoronaphthalene as a molecular igniter; through simple grinding or solvent evaporation and precise co-assembly with octafluoronaphthalene, the photoluminescence quantum yield of solid BPA is increased by 107%, and BPN powder can be lit up from dark to unprecedented bright red. More importantly, the monotonous, weak emission of BPA@BPN, such as yellow, orange, and black, can be significantly adjusted to colorful, brighter emission, such as green, yellow-green, yellow, orange, and red, through crystallization-induced precise co-assembly, and the fluorescence resonance energy transfer efficiency is increased by up to 180% to 270%, solving the problem of high energy dissipation and low FRET efficiency of donor-acceptor pairs with weak aggregated emission in the fluorescence resonance energy transfer process.
[0039] The present invention illustrates the in-depth understanding of the regulation of fluorescence resonance energy transfer through the precise correlation between supramolecular structure and properties. Based on this, the present invention successfully produces different multi-stimulus responsive fluorescence patterns and highly flexible and highly luminous colored flowers.
[0040] The technical scheme of the present invention is further described below through specific examples. In the following examples, the methods described are conventional methods unless otherwise specified; the reagents and materials described are commercially available unless otherwise specified. The room temperature is 20-30°C.
[0041] Example 1
[0042] A co-assembly method for improving the energy transfer efficiency of chromophores comprises the following steps:
[0043] Octafluoronaphthalene with weak fluorescence emission was used as perfluoroaromatic hydrocarbon, 9,10-bis(phenylethynyl)anthracene was used as donor substance, and 5,12-bis(phenylethynyl)tetracene was used as acceptor substance; octafluoronaphthalene, 9,10-bis(phenylethynyl)anthracene and 5,12-bis(phenylethynyl)tetracene were added to tetrahydrofuran according to the total molar amount of acceptor substance and donor substance and the molar amount of perfluoroaromatic hydrocarbon being 1:1; the total mass of octafluoronaphthalene, 9,10-bis(phenylethynyl)anthracene and 5,12-bis(phenylethynyl)tetracene and tetrahydrofuran were used in a ratio of 1mg:1mL. After being mixed evenly, the mixture was evaporated at room temperature and atmospheric pressure to remove the solvent, and a one-dimensional needle-shaped eutectic was prepared, i.e., a precise co-assembled supramolecular structure, denoted as BPA / BPN-OFN, with a length of up to tens of microns.
[0044] Table 1 Ratio of BPA and BPN at different molar percentages
[0045]
[0046]
[0047] Example 2
[0048] A co-assembly method for improving the energy transfer efficiency of chromophores comprises the following steps:
[0049] After 0.1mol of octafluoronaphthalene, 0.08mol of 9,10-bis(phenylethynyl)anthracene and 0.02mol of 5,12-bis(phenylethynyl)tetracene were mixed evenly, tetrahydrofuran was added; the total mass of octafluoronaphthalene, 9,10-bis(phenylethynyl)anthracene and 5,12-bis(phenylethynyl)tetracene and the amount of tetrahydrofuran was 10mg:0.05mL. Grinding was performed at room temperature for 20s to 30s until the solvent evaporated completely, and a one-dimensional needle-shaped co-crystal was prepared, which was a precise co-assembled supramolecular structure, recorded as BPA / BPN-OFN.
[0050] Example 3
[0051] A co-assembly method for improving the energy transfer efficiency of chromophores comprises the following steps:
[0052] Octafluoronaphthalene with weak fluorescence emission is used as perfluoroarene, and 9,10-bis(phenylethynyl)anthracene is used as an aromatic donor; octafluoronaphthalene and 9,10-bis(phenylethynyl)anthracene are added to tetrahydrofuran in a molar ratio of 1:1, and the total mass of octafluoronaphthalene and 9,10-bis(phenylethynyl)anthracene and tetrahydrofuran is 1 mg:1 mL; after uniform mixing, the mixture is evaporated at room temperature and normal pressure to remove the solvent, thereby preparing an aromatic-perfluoroarene eutectic, which is recorded as BPA-OFN.
[0053] Example 4
[0054] A co-assembly method for improving the energy transfer efficiency of chromophores comprises the following steps:
[0055] Octafluoronaphthalene with weak fluorescence emission is used as perfluoroarene, and 5,12-bis(phenylethynyl)tetracene is used as an aromatic donor; octafluoronaphthalene and 5,12-bis(phenylethynyl)tetracene are added to tetrahydrofuran in a molar ratio of 1:1, and the total mass of octafluoronaphthalene and 5,12-bis(phenylethynyl)tetracene and tetrahydrofuran is 1 mg:1 mL; after being mixed evenly, the mixture is evaporated at room temperature and normal pressure to remove the solvent, thereby preparing an aromatic-perfluoroarene eutectic, which is recorded as BPN-OFN.
[0056] Example 5
[0057] A co-assembly method for improving the energy transfer efficiency of chromophores comprises the following steps:
[0058] Octafluoronaphthalene with weak fluorescence emission is used as perfluoroarene, and 9,10-bis(phenylethynyl)anthracene is used as an aromatic donor; octafluoronaphthalene and 9,10-bis(phenylethynyl)anthracene are added to tetrahydrofuran in a molar ratio of 1:1, and the total mass of octafluoronaphthalene and 9,10-bis(phenylethynyl)anthracene and tetrahydrofuran is 10 mg:0.05 mL; grinding is performed at room temperature for 20s to 30s until the solvent is completely evaporated, and an aromatic hydrocarbon-perfluoroarene eutectic is prepared, which is recorded as BPA-OFN.
[0059] Example 6
[0060] A co-assembly method for improving the energy transfer efficiency of chromophores comprises the following steps:
[0061] Octafluoronaphthalene with weak fluorescence emission is used as perfluoroarene, and 5,12-bis(phenylethynyl)tetracene is used as an aromatic donor; octafluoronaphthalene and 5,12-bis(phenylethynyl)tetracene are added to tetrahydrofuran in a molar ratio of 1:1, and the total mass of octafluoronaphthalene and 5,12-bis(phenylethynyl)tetracene and tetrahydrofuran is 10 mg:0.05 mL; grinding is performed at room temperature for 20s to 30s until the solvent is completely evaporated, and an aromatic hydrocarbon-perfluoroarene eutectic is prepared, which is recorded as BPN-OFN.
[0062] Example 7
[0063] A co-assembly method for improving the energy transfer efficiency of chromophores comprises the following steps:
[0064] The BPA-OFN prepared in Example 3 and the BPN-OFN prepared in Example 4 were added to tetrahydrofuran, and the total mass ratio of BPA-OFN and BPN-OFN to tetrahydrofuran was 1 mg: 1 mL; after being uniformly mixed, the mixture was evaporated at room temperature and normal pressure to remove the solvent, thereby preparing an aromatic hydrocarbon-perfluoroaromatic hydrocarbon eutectic, which was recorded as BPA-OFN@BPN-OFN.
[0065] Table 2 Ratios of BPA-OFN and BPN-OFN with different molar percentages
[0066] Group BPA-OFN BPN-OFN product B1 100% 0 BPA-OFN B2 99.7% 0.3% BPA-OFN@BPN-OFN - 0.3% B3 96.3% 3.7% BPA-OFN@BPN-OFN - 3.7% B4 87.6% 22.4% BPA-OFN@BPN-OFN - 22.4%
[0067] Test 1: Photophysical property analysis.
[0068] BPA solid, 0.1 mg / mL BPA solution and BPA-OFN prepared in Example 3 were observed and analyzed under 365 nm ultraviolet irradiation. The results are shown in Figure 1 and Table 3. BPN solid, 0.1 mg / mL BPN solution and BPN-OFN prepared in Example 4 were observed and analyzed under 365 nm ultraviolet irradiation. The results are shown in Figure 2and Table 3. The BPA solution is prepared by mixing BPA with tetrahydrofuran; and the BPN solution is prepared by mixing BPN with tetrahydrofuran.
[0069] Table 3 Photophysical properties analysis results
[0070]
[0071] Depend on Figure 1 and Figure 2 It can be seen that the significantly regulated photophysical properties of BPA-OFN and BPN-OFN can be directly judged by the naked eye. After co-assembly with the colorless weak-emitting OFN, the color of BPA changed from orange-red to green, and the color of BPN changed from black to red. After co-assembly, the photoluminescence quantum yield of BPA-OFN was 29.03%, and the photoluminescence quantum yield of BPN-OFN was 4.73%, showing brighter luminescence compared with BPA solid and BPN solid. Moreover, the emission color of the co-crystal is consistent with the emission color of its corresponding single-component aromatic solution. In Examples 5 and 6, by simple solvent-assisted grinding, according to the drastic change in color, it can be observed that the aromatic donor and OFN gradually approach each other, and finally generate green-emitting BPA-OFN co-crystals and red-emitting BPN-OFN co-crystals.
[0072] The above photophysical property analysis shows that BPA-OFN co-crystals and BPN-OFN co-crystals are effective tools for illuminating solid-state materials with ACQ effect. More importantly, the above preparation method can trigger the interaction between aromatic hydrocarbon donors and perfluoroaromatic hydrocarbons, quickly forming aromatic hydrocarbon-perfluoroaromatic hydrocarbon co-crystals, and the amount of co-crystals prepared reaches the gram level.
[0073] Test 2: Infrared spectroscopy, Raman spectroscopy and powder X-ray diffraction analysis.
[0074] Powder X-ray diffraction, the full name in English, is Powder X-ray Diffraction, abbreviated as PXRD.
[0075] like Figure 3 , CF bond in OFN 784cm -1 After co-assembly with BPA, the CF bond in OFN is red-shifted to 778cm -1 After co-assembly with BPN, the CF bond in OFN was red-shifted to 781 cm -1 In addition, for BPA-OFN, the CF bond in OFN is at 1203 cm -1 The stretching peak at 1193 cm -1 ; For BPN-OFN, the CF bond in OFN is at 1203cm -1 The stretching peak at 1195 cm-1 This shift indicates that the CF bond is weakened and elongated due to the contribution of n→σ* in the arene-perfluoroarene co-crystal. For BPA-OFN, the peak at 947 cm -1 The position corresponds to the side-to-side extension of the CF bond in OFN, which migrates to 944 cm after assembly. -1 ; for BPN-OFN, it migrates to 945cm after assembly -1 After co-assembly, the characteristic stretching peak of Ar-H in BPA increases from 3053 cm -1 Move to 3057cm -1 The characteristic stretching peak of Ar-H in BPN increases from 3052cm -1 Move to 3055cm -1 This change is attributed to the interaction of the halogen bond CF with Ar-H, which indicates the successful stacking between the electron-deficient OFN and the electron-rich aromatics, namely BPA and BPN.
[0076] like Figure 4 , in BPA crystals, the peaks are 395 cm -1 、1218cm -1 、1559cm -1 and 3084cm -1 The Raman spectra of -1 、1221cm -1 、1560cm -1 and 3090cm -1 In BPN crystal, the peaks are at 1179cm -1 、1324cm -1 、1535cm -1 and 2188cm -1 The Raman spectra of the OFN co-assembly shifted to 1180 cm -1 、1325cm -1 、1537cm -1 and 2192cm -1 These results indicate that the electron density of the BPA molecule in the arene-perfluoroarene cocrystals is reduced and further confirm the formation of the arene-perfluoroarene complex.
[0077] The BPA-OFN of Example 3, the BPN-OFN of Example 4, the BPA-OFN of Example 5, and the BPN-OFN of Example 6 were analyzed by powder X-ray diffraction analysis. Figure 5As shown. The samples prepared by simple solvent-assisted grinding in Example 5 and Example 6 showed sharp diffraction peaks, indicating an ordered crystalline superstructure. In addition, the powder X-ray diffraction results of BPA-OFN in Example 5 and BPN-OFN in Example 6 showed a new set of diffraction peaks, which were different from the diffraction peaks of other single components, indicating the generation of new species. These results are consistent with the simulation curves of single crystal structure calculations of samples prepared by solvent evaporation in Example 3 and Example 4, indicating that the molecular stacking of grinding is the same as that of arene-perfluoroarene single crystals. These analyses demonstrate that two arene-perfluoroarene co-crystals were successfully prepared by co-assembly of OFN with two different arene donors.
[0078] Test 3: UV-Vis absorption and photoluminescence spectroscopy.
[0079] To elucidate the photophysical properties of arene-perfluoroarene cocrystals, UV-visible absorption and photoluminescence spectra were recorded and compared with the spectra of the corresponding arene solids and arene dilute solutions, e.g. Figure 6 and Figure 7 The detailed photophysical properties of BPA, BPN, BPA-OFN and BPN-OFN are shown in Table 4.
[0080] Table 4 Key information of aromatic hydrocarbons and prepared co-crystals
[0081]
[0082]
[0083] Note: a The concentration of the BPA solution and the BPN solution was 0.1 mg / mL. b Both BPA solid and BPN solid are powdered solids. c Compared with BPA solid, the absorption wavelength of BPA-OFN has changed; compared with BPN solid, the absorption wavelength of BPN-OFN has changed. d Compared with BPA solid, the emission wavelength of BPA-OFN shifted; compared with BPN solid, the emission wavelength of BPN-OFN shifted. e is the absolute quantum yield obtained by the integrating sphere method, the average of three experiments. f Compared with BPA solid, the photoluminescence quantum yield of BPA-OFN is enhanced; compared with BPN solid, the photoluminescence quantum yield of BPN-OFN is enhanced.
[0084] like Figure 6After co-assembly with OFN molecules with a high band gap of ~3.78eV, the BPA-OFN co-crystals underwent a significant blue shift, and the blue shift values were as high as ~35nm; the BPN-OFN co-crystals underwent a significant blue shift, and the blue shift values were as high as ~66nm. The optical band gap of BPA solid is 2.16eV, the optical band gap of BPN solid is 1.72eV, the optical band gap of BPA-OFN co-crystal is 2.48eV, and the optical band gap of BPB-OFN co-crystal is 1.91eV. When co-crystallized with OFN, the arene-perfluoroarene complexes showed a significant blue shift in emission, with the BPA-OFN co-crystal clearly shifting from 567nm to 487nm, and the BPN-OFN co-crystal clearly shifting from 684nm to 612nm.
[0085] It is noteworthy that the absorption and emission of the cocrystals are largely close to those of the arene solution, indicating that the OFN molecules delicately act as solid solvents and are precisely and periodically inserted into the arene lattice via arene-perfluoroarene interactions. These observations are consistent with Figure 1 and Figure 2 The above blue shift phenomenon is due to the periodic insertion of electron-deficient OFN molecules between two adjacent aromatic molecules through π-π and CH···F interactions, which further blocks the formation of BPA and BPN dimers. This conclusion was confirmed by density functional theory calculations. The blue shift of emission originates from the insertion of OFN molecules screening the π-π interaction between two adjacent aromatic molecules, which can effectively reduce the photoluminescence red shift caused by exciton delocalization.
[0086] Importantly, the photoluminescence quantum yield values of arene-perfluoroarene co-crystals are much higher than those of the above pure arene crystals. Specifically, the photoluminescence quantum yields of BPA-OFN and BPN-OFN increased by 105% (14.18% to 29.03%) and 141% (0.02% to 4.73%), respectively, which are even higher than the photoluminescence quantum yields of the corresponding solutions of BPA, see Table 4.
[0087] The above results indicate that the periodically inserted OFN molecules can effectively disrupt the close-packed structure and aromatic-aromatic dimers in pure aromatic solids through π-π and CH···F interactions. Undoubtedly, the weakly fluorescent OFN with a high band gap of ∼3.78 eV can interrupt the intermolecular interactions and electron exchange between adjacent aromatics, further blocking the SF process and the process of ISC from single state to triple state. Therefore, the non-radiative energy loss of FRET donor BPA molecules and acceptor BPN molecules can be easily suppressed through the crystallization-induced precise co-assembly strategy, paving the way for improving the FRET efficiency between FRET donors and acceptors.
[0088] In order to better understand the regulation of photophysical properties, frontier molecular orbitals were calculated based on the stacking structures of BPA-OFN and BPN-OFN complexes by density functional theory calculations, such as Figure 7 .
[0089] In the BPA-OFN and BPN-OFN co-crystals, the small atomic charge values of the aromatic part are +0.166 and +0.142, respectively. These values are similar and small, indicating that there is almost no charge transfer interaction between OFN and BPA / BPN in these co-crystal structures, which is consistent with the UV absorption results after co-assembly. In addition, the highest and lowest occupied molecular orbitals, HOMO and LUMO, respectively, were calculated to further verify this. After co-assembly with OFN, both HOMO and LUMO are dominated by the orbitals of the aromatic part, indicating the same conclusion that there is no charge transfer interaction between OFN and aromatics.
[0090] Importantly, single crystal X-ray diffraction analysis further confirmed the above packing patterns and intermolecular interactions and revealed structure-photophysical property relationships. As expected, both arene-perfluoroarene superstructures exhibit the same hybrid stacking mode crystal structure, with arene and OFN molecules stacked alternately along the
[001] direction, as shown in Figure 2. Figure 7 Figures E and F show that the molar ratio of the two molecules is 1:1. Specifically, BPA-OFN belongs to the monoclinic space group P21 / c, and the unit cell parameters are α=90°, β=104.471(5)°, γ=90° and The average distance between BPA and OFN is After co-crystallization with OFN, the distance between two adjacent BPAs increased to Similarly, BPN-OFN adopts a face-to-face pattern along its
[001] direction, and the average distance between BPN-OFN is The average distance between BPN-BPN is like Figure 7 BPN-BPN also belongs to the monoclinic space group P21 / c, and the unit cell parameters are α=90°, β=100.157(5)°, γ=90°,
[0091] The average distance between arene-OFN in arene-perfluoroarene cocrystals indicates the presence of π-π interactions between arenes and OFN. In addition, a large number of F···HC bonds are formed between OFN and adjacent arenes, forming a pseudo two-dimensional network on the (001) plane. Therefore, multiple intermolecular interactions, including π-π and halogen bond interactions, stabilize the arene-perfluoroarene cocrystals. These structural analyses further support the above conclusion that OFN molecules are fully inserted into the crystal lattice of the arenes during the cocrystallization process, effectively separating the arene molecules from each other and hindering the interaction and electron exchange between adjacent BPA or BPN molecules. As a result, the triplet state becomes non-existent, such as Figure 1 b, and then the ACQ aromatic molecules exhibit high luminescence efficiency in their aggregated state. In addition, the π-π interaction and halogen bond between aromatics and OFN both lead to the preferential growth of AP cocrystals along the
[100] direction, which is the axial direction, which is conducive to the formation of one-dimensional aromatic-OFN superstructures, such as Figure 7 G and H graphs.
[0092] This was verified using the minimum energy principle of the Materials Studio and predictions based on the minimum energy principle. Figure 7 The calculation results shown in Figures G and H of the graphs show that both arene-perfluoroarene cocrystals grow along the
[100] direction, leading to the formation of a one-dimensional assembly. The morphology of the cocrystals was observed by transmission electron microscopy, which is consistent with the above calculation results. In addition, an attempt was made to further confirm the cocrystal structure by selected area electron diffraction. However, no lattice was observed, which should be due to the high energy of electron beam irradiation, which can destroy the organic crystal structure.
[0093] Test 4: Absorption and photoluminescence spectra.
[0094] Under the premise of satisfying the three elements of fluorescence resonance energy transfer, namely sufficient spectral overlap, DA distance <10nm and well-oriented DA dipoles, the lattice parameters of BPA-OFN and BPN-OFN crystal units lay the foundation for the fluorescence resonance energy transfer process between BPN-OFN doped into BPA-OFN host and energetic DA pairs. Among them, green-emitting BPA-OFN and red-emitting BPN-OFN can act as energy donors and energy acceptors, respectively. These characteristics, coupled with the unique function of OFN to suppress non-radiative energy dissipation, lead to the speculation that the strategy of crystallization-induced precise co-assembly to improve the efficiency of fluorescence resonance energy transfer between BPA and BPN is very feasible.
[0095] To achieve this goal, a small amount of BPN-OFN was introduced into BPA-OFN by simple grinding or solvent evaporation. For comparison, fluorescence resonance energy transfer experiments were also performed on the BPA-BPN pair without OFN by adding a small amount of BPA to BPN. The absorption spectra of BPN and BPN-OFN and the emission spectra of BPA and BPA-OFN are shown in Figure 2. Figure 8 As shown. Obviously, in the wavelength range of 490nm to 650nm, the fluorescence spectrum of BPA overlaps well with the absorption spectrum of BPN. Similarly, the emission spectrum of BPA-OFN and the absorption spectrum of BPN-OFN also overlap well in the wavelength range of 450nm to 700nm. These results indicate that fluorescence resonance energy transfer may occur from BPA donor to BPN acceptor, or from BPA-OFN to BPN-OFN. This verifies the strategy of the above embodiments of the present invention. Figure 8 As shown in Tables 1 and 2, at low doping ratios of 0.3% and 3.7%, the corresponding absorption bands of BPA-OFN@BPN-OFN have almost no change relative to pure donor BPA and BPA-OFN. At a doping ratio of 22.4%, new weak absorption peaks can be found, which are obviously from pure acceptor BPN and BPN-OFN. In addition, compared with the BPA@BPN system without OFN, the absorption spectrum of the BPA-OFN@BPN-OFN system is blue-shifted by 35nm due to the periodic insertion of OFN.
[0096] The corresponding steady-state emission spectra of BPA@BPN or BPA-OFN@BPN-OFN microrod films were analyzed. For BPA@BPN, the 537nm emission peak of BPA was red-shifted to 596nm. In addition, under 365nm UV irradiation, the corresponding photos of the doped BPA@BPN film showed a monotonous emission from yellow to red to dark with the increase of BPN doping rate. The photoluminescence quantum yields of BPA, BPA@BPN-0.3%, BPA@BPN-3.7%, BPA@BPN-22.4% and BPN were 14.18%, 10.65%, 8.88%, 1.87% and 0.02%, respectively. It shows that the fluorescence emission has been significantly regulated.
[0097] In sharp contrast, by using OFN involved in crystallization-induced precise co-assembly, BPA-OFN@BPN-OFN exhibits tunable fluorescence, emitting brighter and wider spectral range. In such fluorescence resonance energy transfer system, when a small amount of BPN-OFN is used as dopant, BPN-OFN pairs can replace π-π similar crystal structure as well as BPA-OFN complex and halogen bonds through BPA-OFN pairs. When the doping rate increases to 22.4%, the emission band at 487 nm from BPA-OFN components can be gradually suppressed, while those at 553 nm caused by BPN-OFN are greatly enhanced, indicating that effective isotope occurs from BPA-OFN donor to BPN-OFN acceptor. In addition, the emission band of BPA-OFN@BPN-OFN at 553 nm is blue-shifted from that of pure BPN-OFN crystal at 612 nm, which should be due to the solid dispersion effect of BPN-OFN with a large amount of BPA-OFN.
[0098] Under ultraviolet light excitation, as the doping rate of BPN-OFN increases, the corresponding microrod film can achieve emission colors from green to yellow to orange to red. The quantum yields of BPA-OFN microrods and BPA-OFN@BPN-OFN microrods with different doping amounts are 29.03%, 32.46%, 34.77%, 31.80% and 4.73%, respectively, which are much higher than pure BPA and BPA / BPN-OFN with different doping amounts.
[0099] The efficient fluorescence of BPA-OFN@BPN-OFN should be attributed to the lighter effect of the OFN component.
[0100] Table 5 Key information of FRET complex
[0101] name t / ns <![CDATA[Absolute quantum yield / % a > <![CDATA[E / % b ]]> <![CDATA[Improvement / % c > BPA Solids 10.00 14.18 - - BPA / BPN-OFN-0.3% 9.68 10.65 3.2 0 BPA / BPN-OFN - 3.7% 9.44 8.88 5.6 0 BPA / BPN-OFN - 22.4% 8.70 1.87 13.0 0 BPN Solid 7.45 0.02 - - BPA-OFN 16.61 29.03 - - BPA-OFN@BPN-OFN - 0.3% 15.11 32.46 9.0 181 BPA-OFN@BPN-OFN - 3.7% 13.24 34.77 20.3 263 BPA-OFN@BPN-OFN - 22.4% 9.26 31.80 44.3 241 BPN-OFN 1.34 4.73 - -
[0102] Note: a Absolute quantum yield obtained by integrating sphere method, average of three experiments. b Fluorescence resonance energy transfer efficiency, according to Calculate, where E is the FRET efficiency, which is a value between 0 and 1; t DA is the fluorescence lifetime when the donor substance and the acceptor substance coexist; t D is the fluorescence lifetime when the donor substance exists alone. c Compared with the fluorescence resonance energy transfer without OFN, the fluorescence resonance energy transfer efficiency of the fluorescence resonance energy transfer complex with OFN is improved.
[0103] In addition, in order to study the effect of OFN incorporation on the fluorescence resonance energy transfer efficiency, the time-resolved fluorescence decay spectra of BPA@BPN and BPA-OFN@BPN-OFN fluorescence resonance energy transfer systems deposited on quartz substrates were tested. Figure 8 As shown in Figure 2, the fluorescence lifetime of pure BPA microrods is about 10.00ns. When the BPN doping ratio is 0.3%, 3.7%, and 22.4%, the fluorescence lifetime can be reduced to 9.68ns, 9.44ns, and 8.70ns, respectively. Since fluorescence resonance energy transfer provides an additional de-excitation pathway, it will enhance the excited state decay of the donor, thereby shortening its fluorescence lifetime. Differently, the fluorescence lifetimes of BPA-OFN and BPN-OFN complexes are 16.61 and 1.34ns, respectively. Figure 8 When BPN-OFN was doped with different ratios of 0.3%, 3.7%, and 22.4%, the lifetime of BPA-OFN gradually shortened to 15.11, 13.24, and 9.26 ns, respectively. These results provide strong additional evidence to support the direct energy transfer process from BPA to BPN and the FRET process between BPA-OFN and BPN-OFN through non-radiative dipole-dipole interaction.
[0104] In addition, in order to further understand the effect of OFN insertion on the fluorescence resonance energy transfer process between the BPA-BPN pair, the FRET efficiency of the BPA@BPN and BPA-OFN@BPN-OFN systems at different doping ratios was calculated according to the FRET efficiency calculation formula, as shown in Table 5. Compared with BPA@BPN, the FRET efficiency of the fluorescence resonance energy transfer system containing OFN can be significantly improved. For example, the doping ratios are 0.3%, 3.7% and 22.4%, 3.2%, 13.0%, 9.0%, 20.3% and 44.3%, that is, the FRET efficiency is increased by 181%, 263% and 241%, respectively.
[0105] When excited by UV light, pure BPA-OFN microrods emit strong green light, while doped BPA-OFN microrods show uniform and tunable emission colors from green to yellow to orange and then red when increasing the doping ratio of BPN-OFN from 0.3% to 22.4%, as shown in Figure 2. Fig. 9 , which is consistent with the emission color of the corresponding microrod film. At the same time, this observation presents a uniform emission regardless of the doping ratio of BPN-OFN, indicating that the BPN molecules are uniformly dispersed in the BPA-OFN host, which is also confirmed by PXRD, as shown in Fig.10After introducing a small amount of BPN as a dopant, the PXRD patterns of the fluorescence resonance energy transfer complexes show that they are still highly crystalline and mainly originate from the BPA-OFN component. In fact, even when the doping ratio reaches 3.7%, no XRD peaks of the BPN-OFN component are found, and only very weak features can be found until the doping concentration is increased to 22.4%.
[0106] Therefore, it can be inferred that the high doping ratio of BPN-OFN does not cause phase separation in the FRET system, indicating that each FRET microrod is composed of an almost uniform composition and a precise mixed stacking structure. In addition, in order to more accurately compare the emission colors, Fig.11 The CIE chromaticity diagram of the prepared samples is provided. The color coordinate values of BPA-OFN, three doped fluorescence resonance energy transfer complexes and BPN-OFN calculated based on their PL spectra are (0.36, 0.53), (0.42, 0.53), (0.46, 0.52), (0.50, 0.49) and (0.63, 0.37), respectively. The corresponding colors in CIE are consistent with the above experimental results.
[0107] The energy transfer mechanism of doped BPA-OFN, such as Fig.12 As shown, energy is transferred from excited BPA-OFN to BPN-OFN due to the following prerequisites. First, the donor-acceptor pair of BPA-OFN / BPN-OFN meets the structural requirements, namely, a well-matched stacking pattern as indicated by the structural analysis. Second, the emission spectrum of BPA-OFN is found to overlap well with the absorption spectrum of BPN-OFN, which provides another condition for fluorescence resonance energy transfer. In addition, due to the good dispersion of BPN molecules in the BPA-OFN matrix, a suitable distance can be achieved between BPA-OFN and BPN-OFN.
[0108] In addition to the above three prerequisites, the FRET efficiency also depends on other parameters, such as the fluorescence lifetime and photoluminescence quantum yield value of the donor, as well as the quenching efficiency of the acceptor. Therefore, a significant improvement in FRET efficiency can be achieved in BPA-OFN@BPN-OFN compared with the BPA@BPN system without OFN, which is due to the highly increased photoluminescence quantum yield induced by OFN.
[0109] The physical processes involved in fluorescence resonance energy transfer are as follows: First, the energy absorption of the donor leads to their excitation from the ground state to the excited singlet state. Second, possible FRET from the excited donor includes spontaneous emission and non-radiative processes. At the same time, if a proximal energy acceptor is available, non-radiative FRET from the energy donor to the energy acceptor can occur, such as Fig.12. Under non-radiative light excitation, the electronic energy of the excited-state donor can be transferred to the ground-state acceptor. Therefore, the emission of the donor will be quenched by the acceptor. By adjusting the dopant ratio, the green emission of BPA-OFN will be partially quenched, while the red emission of BPN-OFN will be enhanced accordingly, resulting in tunable emission. Notably, this simple method to improve the FRET efficiency and reduce the energy loss during FRET has not been reported before, which may serve as an advanced strategy to develop highly emissive organic supramolecular light harvesting systems with high FRET efficiency. This can be easily achieved by precisely doping OFN into commercially available donor-acceptor pairs with ACQ effect by simple grinding or solvent evaporation.
[0110] Application Examples
[0111] The above-mentioned adjustable excited-state OFN insertion and energy acceptor doping strategy achieves high efficiency and strong fluorescence emission with controllable fluorescence color, e.g. Figure 8 to Figure 12 As shown, this strategy combined with a simple preparation method makes it possible to explore the applications of the corresponding crystals in advanced fluorescent inks and multi-stimulus responsive fluorescent systems, such as Fig.13 , demonstrating its potential application value in multiple fields.
[0112] First, the water dispersion of these materials was easily achieved through a water / surfactant-mediated grinding process using polyvinyl alcohol (PVA) surfactant, resulting in a uniform fully water-dispersible fluorescent ink with the same luminescence as the solid sample. Subsequently, a multi-stimulus-responsive fluorescent system was successfully prepared based on the strong intermolecular interactions and similar lattices of BPA-OFN and BPN-OFN.
[0113] like Fig.13 , two brushes dipped in yellow BPA and black BPN ink were used to draw the letters of FRET and By XJTU and a cartoon picture of a thumb respectively. Under ultraviolet light, the letters of FRET are easily distinguished due to the yellow fluorescence of BPA, while the letters of By XJTU and the cartoon thumb disappear due to the dark emission of BPN.
[0114] When the OFN solution was used to draw on the painting, the weak yellow emitting FRET letters immediately turned into strong green emission, while the non-luminescent black By XJTU letters and the cartoon picture of the thumb were successfully illuminated and visualized. This observation is similar to the fluorescence changes after BPA and BPN were co-assembled with OFN, indicating that BPA-OFN and BPN-OFN cocrystals were generated under the stimulation of OFN solution.
[0115] Subsequently, the letters R, E, and T were drawn in sequence using the BPN-OFN solution as the concentration increased. As expected, the three green-emitting letters turned into yellow, orange, and orange-red emission, respectively, indicating that BPA-OFN@BPN-OFN formed an efficient and highly efficient fluorescence resonance energy transfer complex. Therefore, the letter F with green emission, the letter R with yellow emission, the letter E and T with orange emission, and the letter By XJTU with orange-red emission are easily distinguished, as shown in Figure 2. Fig.13 The d-image finally forms a colorful painting. This stimuli-fluorescence color change result shows that this material has good potential in advanced fully water-dispersible fluorescent inks and anti-fake fluorescent recording.
[0116] Even more impressively, the aqueous luminescent ink can also be used to prepare thin films with high emission through a simple doctor-blade coating technique, e.g. Fig.13 e figure. It is worth noting that the synthesized light-emitting film has ultra-flexible properties, which is convenient for free bending, folding and cutting. Coupled with the high emission characteristics, it promotes the application of such materials in advanced manufacturing and packaging. Based on these advantages, three high-emitting flowers were successfully prepared using yellow-emitting BPA-OFN@BPN-OFN-0.3%, orange-emitting BPA-OFN@BPN-OFN-3.7%, and red-emitting BPN-OFN films as petals, and green-emitting BPA-OFN films were used to make leaves, such as Fig.13 In the e-image, BPA-OFN, BPA-OFN@BPN-OFN-0.3%, BPA-OFN@BPN-OFN-3.7% and BPN-OFN are green, yellow, orange and red respectively. This attempt shows that aqueous luminescent ink has great application potential in the field of advanced luminescent craft art, and combined with the above research on stimuli-responsive fluorescent painting, it shows the versatility of this aqueous luminescent ink.
[0117] In summary, the embodiments of the present invention propose a novel and simple method, namely, crystallization-induced precise co-assembly, to significantly improve the fluorescence resonance energy transfer efficiency of donor-acceptor pairs with ACQ effect, such as BPA as donor and BPN as acceptor. In this strategy, weakly fluorescent OFN is cleverly used as a molecular igniter to promote the precise co-assembly of BPA and BPN during the crystallization process. Since BPA and BPN have a high degree of spectral overlap, but each has a significant ACQ effect, this co-assembly method effectively overcomes this problem and realizes an efficient FRET process.
[0118] The present invention achieves precise co-assembly of BPA and BPN under the mediation of weak fluorescent OFN through simple grinding or solvent evaporation methods. This innovative strategy significantly improves the photoluminescence quantum yield of BPA solids by up to 107%, and for the first time lights up the originally dim BPN solids, showing bright red fluorescence. More importantly, the originally monotonous and weak FRET emission of BPA@BPN, such as yellow, orange, and dark colors, is significantly adjusted to colorful and brighter emission, such as green, yellow-green, yellow, orange, and red, after this co-assembly process, and the FRET efficiency is improved by 180% to 270%.
[0119] By deeply exploring the precise relationship between supramolecular structure and properties, the present invention reveals the deep mechanism of FRET efficiency improvement and provides a new perspective for understanding and regulating the FRET process. In addition, this strategy gives BPA / BPN excellent anti-counterfeiting properties and artistic application potential, and has been successfully applied to the production of unique multi-stimulus responsive fluorescent patterns and colorful flowers with high flexibility and high emission intensity. The embodiments of the present invention not only provide a rare and critical solution for improving the FRET efficiency of ACQ donor-acceptor pairs, but also greatly broaden the research and application fields of ACQ molecules, and provide important references and inspirations for FRET regulation strategies in other organic systems.
[0120] The above are only preferred embodiments of the present invention and are not intended to limit the present invention. Any modifications, equivalent substitutions and improvements made within the spirit and principles of the present invention should be included in the protection scope of the present invention.
Claims
1. A co-assembly method for improving the energy transfer efficiency of chromophores, characterized in that: The following steps are involved: Co-assembling a donor substance and a perfluoroarene in a solvent system to prepare a donor-perfluoroarene complex; co-assembling an acceptor substance and a perfluoroarene in a solvent system to prepare an acceptor-perfluoroarene complex; Co-assembling a donor-perfluoroarene complex and an acceptor-perfluoroarene complex in a solvent system, and inserting the perfluoroarene into the crystal lattices of the donor substance and the acceptor substance during the co-assembly process to prepare a co-assembly; The donor substance is 9,10-bis(phenylethynyl)anthracene; the acceptor substance is 5,12-bis(phenylethynyl)tetracene; and the perfluoroaromatic hydrocarbon is octafluoronaphthalene.
2. The co-assembly method for improving chromophore energy transfer efficiency according to claim 1, characterized in that: The ratio of the total molar amount of the acceptor substance and the donor substance to the molar amount of the perfluoroarene is 1:
1.
3. The co-assembly method for improving chromophore energy transfer efficiency according to claim 1, characterized in that: The percentage of the molar amount of the acceptor substance to the total molar amount of the donor substance and the acceptor substance is 0.3% to 22.4%.
4. The co-assembly method for improving chromophore energy transfer efficiency according to claim 1, characterized in that: The solvents used to prepare the donor-perfluoroarene complex, the acceptor-perfluoroarene complex and the co-assembly are respectively selected from at least one of chloroform, N,N-dimethylformamide, tetrahydrofuran, acetone and acetonitrile.
5. The co-assembly method for improving chromophore energy transfer efficiency according to claim 4, characterized in that: The co-assembly is performed by wet grinding in a solvent system, or by volatilization in a solvent system to remove the solvent.
6. The co-assembly method for improving chromophore energy transfer efficiency according to claim 1, characterized in that: In the co-assembly, the average distance between the donor substance and the acceptor substance is 0.69-0.7 nm.
7. A co-assembly, characterized in that: The co-assembly is prepared by the co-assembly method for improving the chromophore energy transfer efficiency as described in any one of claims 1 to 6.
8. The co-assembly according to claim 7, characterized in that: The crystal parameters of the donor-perfluoroarene complex are: monoclinic space group P21 / c, unit cell parameters α=90°, β=104.471(5)°, γ=90° and 9. The co-assembly according to claim 8, characterized in that The crystal parameters of the receptor-perfluoroarene complex are: monoclinic space group P21 / c, unit cell parameters α=90°, β=100.157(5)°, γ=90°, 10. Use of the co-assembly according to claim 7 in preparing water-phase luminescent ink.
Citation Information
Patent Citations
Application of octafluoronaphthalene eutectic supramolecular material in photocatalytic degradation
CN116078428A
Application of molecular eutectic material in photocatalytic synthesis of hydrogen peroxide
CN117585647A
Cited By
AIE matrix-coated efficient FRET-ISC synergistic composite photosensitive nano-material and preparation method and application of AIE matrix-coated efficient FRET-ISC synergistic composite photosensitive nano-material
CN121571199A